Analisis Evaluasi Pembelajaran Digital Berbasis Game Edukasi Quizizz Bagi Guru Sekolah Menengah Pertama Karimunjawa (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The main priority problems faced by partners are the lack of knowledge of digital learning evaluation and the absence of Quizizz that can be offered to the community. So that the solution offered is to increase the evaluation capacity of Quizizz-based digital learning at SMPN 1 Karimunja-wa. The solution was implemented in the form of a Quizizz Development workshop for SMPN 1 Karimunjawa, a digital learning evaluation facilitator workshop, Quizizz development for SMPN 1 Karimunjawa; and making Quizizz-based digital learning evaluation simulation videos. In general, the implementation of activities using the Quizizz-based digital learning evaluation model approach is divided into four stages, namely the preparation stage, the implementation stage, and the evaluation and monitoring stage. The effort for program sustainability is through implementation assistance to students. Program sustainability is also pursued by building partnerships between SMP/MTs with various parties in the Karimunjawa District, such as SMPN 2 Karimunjawa, MTs Safinatul Huda 2 Karimunjawa, and various parties engaged in learning evaluation. Based on the evaluation analysis after the activity, it was found that there was an increase in knowledge of 86% about the use of Quizizz Educational Games in learning evaluation.